Ramification of Metacognition and Cognitive Styles on Thinking Styles with impeding effect of Cognitive Rigidity in Engineers - Garima Saini, Ms.; Shabnam, (International Journal of Psychosocial Rehabilitation, 2020)
This paper establishes a connection between concepts of thinking styles in conjunction with cognitive psychology. The eventual goal is the development of a deeper understanding and a formal methodology by examining the repercussions of metacognition and cognitive styles on thinking styles. The mediating role of cognitive rigidity with cognitive styles, metacognition, and thinking styles is also assessed. A sample of 205 engineers from different public and private engineering firms was taken, which were used for data analysis. SPSS 22.0 and partial least squares (PLS) analysis with Smart PLS 3.0 software are used. Structural analysis was applied and suggested that cognitive styles and metacognition influence the thinking styles and the way the task is performed. Moreover, cognitive rigidity, stress, depression, and anxiety mediate the relationship between cognitive styles, metacognition, and thinking styles. The thinking style in context to cognitive styles, metacognition, helps in understanding and improving the efficiency by planning, evaluating, monitoring, and implication of the task that they are performing. Stress, anxiety, and depression act as cognitive rigidities that hamper and impede the metacognition and cognitive styles. Implications, suggestions, and limitations for future research are also provided.